Comparison Of Work Intensity With pre-prandial blood sugar level, Uric Acid, And Total Cholesterol Between staff In Nusa Cendana faculty of Medicine And Veterinary Medicine With Workers In Class IIA Prison In Kupang - Alexander Shintu Salem (Cendana Medical Journal, 2025)
Abstract Background: Diabetes mellitus, uric acid and cholesterol are part of non- communicable diseases (PTM) whose prevalence is increasing globally every year. Risk factors for Diabetes mellitus include hypertension, dyslipidemia, unhealthy diet, obesity, and lack of physical activity. In line with the risk factors for diabetes, there are similarities in the risk factors for uric acid and cholesterol, namely habits such as smoking, drinking alcohol, unhealthy diet and lack of physical activity will increase the risk. Several studies have shown that the intensity of work that uses more physical activity affects the results of pre- prandial blood sugar level (GDS), uric acid and total cholesterol. Purpose: To analyze the Comparison Of Work Intensity With pre-prandial blood sugar level, Uric Acid, And Total Cholesterol Between Nusa Cendana faculty of Medicine And Veterinary staff With Workers In Class IIA Prison In Kupang. Method: This research is an observational analytic study with a cross-sectional design which was conducted on FKKH staff at Nusa Cendana University and workers at Class IIA Kupang prison through observation, measurement, observation of the observed objects as well as interviews and structured questionnaire filling of research subjects. Pre-prandial blood sugar level, uric acid, and total cholesterol were checked for the study respondents. The number of respondents was 31 FKKH Undana employees and 31 workers at Class IIA Kupang prison, so that the total number of respondents was 62 respondents who met the inclusion and exclusion criteria. The research was analyzed using univariate, different tests and comparisons using Mann Whitney statistics with a ρ-value of 0.05 which were processed using the SPSS program. Result: The results of the comparative test statistical analysis showed that there were significant differences in the variables of pre-prandial blood sugar level (p=0.030) and total cholesterol (p=0.003) between groups of employees at FKKH Undana and workers at Class IIA Kupang prison. Meanwhile, there was no significant difference between the uric acid variable between the employee groups at FKKH Undana and workers at Class IIA Kupang prison (p=0.398). Conclusion: There were significant differences in pre-prandial blood sugar level and total cholesterol examinations, but there were no significant differences in uric acid values between FKKH staff at Nusa Cendana University and workers at Class IIA Kupang prison. Keywords: GDS, Uric Acid, Total Cholesterol, Work Intensity, FKKH Employees, Prison Workers